Seseli besserianum (Apiaceae), a restored species and a replacement name for Seseli peucedanifolium Besser - Stoyanov, Stoyan; Ostroumova, Tatiana; Degtjareva, Galina; Samigullin, Tahir (Phytotaxa, 2020)
The taxonomic status of Seseli peucedanifolium Besser, a little-known and neglected species in the Bulgarian flora, has been revisited. The study of its morphology, fruit anatomy and sequence data (ITS and ETS) revealed that it should not be treated at infraspecific rank under S. rigidum or synonymized with S. tortuosum or S. arenarium. Seseli besserianum nom. nov. is herein proposed as a replacement name for S. peucedanifolium Besser, a later homonym of S. peucedanifolium Mérat.